Pengelolaan Sampah Plastik sebagai Ancaman Keamanan Maritim di Indonesia di Kabupaten Pandeglang - Laode Muhamad Fathun, Laode Muhamad Fathun; I Nyoman Aji Suadhana Ray, I Nyoman Aji Suadhana Ray (Jurnal Keamanan Nasional, 2019)
This research purpose the issue of maritime security through. One of the maritime security issues in Indonesia is the issue of waste management at sea. As a country that wants to establish itself as the world’s maritime axis, it should make waste at sea an important issue and need serious attention. Research from Ocean Conservancy reports that around 8 million tons of plastic pass into the sea every year. If the condition cannot be controlled, by 2025 about 1 ton of plastic waste will be found in every 3 tons of fish taken from the sea. This research was conducted in Pandelela Region, Banten Province from May to December 2019. This study wanted to look at the marine waste management challenge in Pandeglang District and its completion strategy. With the case study method through a qualitative research paradigm with data collection techniques, field observations, interviews, and literature review, the results were obtained while that waste management in Pandeglang Region has not been a government priority. The government is still focusing on poverty, education and health issues. To 2020 and has been included in the regional strategic plan. Challenges obtained in waste management are problems of policy orientation, economic problems, cultural issues, and resources. For this reason, hopefully, this study can be useful for many parties, including government, academia, students and the community.